Shuvra-yi inqilab va dulat-i muvaqqat : . Simai-yi dulati muvaqqat az viladat ta rihlat (Nihzat-i Azadi-yi Iran)
The Council of the Islamic Revolution and the interim government, an open letter by Bazargan to Imam [Khumaini], the image of the interim government from birth to death.